Evaluación técnico-financiera del completamiento dual para un pozo tipo del bloque Cubiro (2016)
This work evaluates the design of a dual completion that allows the production of two reservoirs simultaneously without mixing, in a well type on "Bloque Cubiro" which have a bottom casing of 9 5/8. The dual completions manage two production tubing can be arranged in differents configurations, either in parallel or concentrically to handle formations independently determining that proper for the well is the concentric completion due to space restrictions. Through a selection matrix that evaluates qualitatively and quantitatively conventional artificial lift systems with the features present in the well of Block Cubiro, it is determined that the optimum lifting is Electrosubmersible pumping (ESP).